Planktonic foraminifera transfer function approach to Red Sea paleoceanography - Siccha, Michael (Universität Tübingen, 2009)
This study examines the potential of using the assemblage composition of planktonic foraminifera in the Red Sea as a quantitative proxy for paleoclimate reconstructions. To this end, a new surface sediment sample dataset was generated to evaluate the environmental control on foraminifera assemblages and to serve as the calibration dataset for the subsequent development of planktonic foraminifera transfer functions. Gradient analysis was employed to investigate the effect of temperature, salinity, primary productivity, water column stratification and the properties of the oxygen minimum zone on the foraminifera fauna of the Red Sea. Because of the high mutual correlation among all environmental parameters along the basin axis, no unambiguous identification of the controlling parameter could be achieved by statistical analyses of the calibration dataset alone. A comparison with published studies on the ecology of planktonic foraminifera, however, lead to the working hypothesis that primary productivity determines the distinct gradient in the foraminifera community in the Red Sea. Transfer functions were then generated by four mathematical methods to characterise the relationship between foraminifera assemblages and chlorophyll a concentration as a proxy for productivity. The transfer functions appear highly efficient in capturing the modern productivity gradient in the Red Sea, with an average root mean squared error of prediction of 0.124 mg/m³, corresponding to 10.3% of the observed gradient. The working hypothesis was then tested and on two newly generated Holocene faunal records from the central and northern Red Sea. Apart from the impact of sea level on the hydrography of the Red Sea, these records showed a strong influence of the dominant regional climatic system, the Indian monsoon. The reconstructed chlorophyll a concentrations indicate low productivity for the early Holocene, which can be ascribed to lowered sea level and a strong SW monsoon. An earlier postglacial recovery of the fauna in the northern ...